Composite material for improving utilization rate of solar blue-green photocatalytic degradation water pollutants

By growing Cu-ZnO nanocomposites on wood, the problem of low utilization rate of existing semiconductor photocatalysts on blue-green light is solved, and efficient utilization of blue-green light and effective degradation of water pollutants is achieved.

CN119500277AInactive Publication Date: 2025-02-25PANZHIHUA RONGZE VANADIUM & TITANIUM CO LTD

Patent Information

Application Number
CN202411649064.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing semiconductor photocatalysts have fewer applications in the blue-green band that accounts for a large proportion of sunlight, resulting in low overall catalytic efficiency.

Method used

Cu-ZnO nanocomposites are prepared by doping copper ions and grown on the inside and surface of decolorized wood to form composite materials with catalyst growth in a resonant cavity.

Benefits of technology

The utilization rate of semiconductor catalysts on blue-green light visible bands of sunlight has been significantly improved, and the efficiency of catalytic degradation of water pollutants has been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500277A_ABST
    Figure CN119500277A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a composite material for improving the utilization rate of solar blue-green photocatalytic degradation of water pollutants, which comprises the following steps: firstly, preparing a Cu-ZnO nano composite material by doping zinc oxide with copper ions, and reducing the forbidden band width, so that the Cu-ZnO nano composite material can utilize sunlight with longer wavelength, and the absorption peak of the Cu-ZnO nano composite material generates red shift; secondly, decolorizing the wood by adopting an alkaline sodium sulfate method, removing lignin in the wood to leave a cavity, and growing the Cu-ZnO nano composite material in the treated wood and on the surface of the treated wood by adopting a hydrothermal method to form a composite material with a catalyst growing in a similar resonant cavity, as shown in Figure 1; the utilization rate of a semiconductor catalyst to blue-green light is improved, a cavity structure formed by the treated wood can have a certain local effect on long-wavelength light, the purpose of fully utilizing long-wave sunlight for multiple times is achieved, and the blue-green photocatalytic efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of semiconductor materials, and in particular relates to a composite material for improving the utilization rate of solar blue-green light catalytic degradation of water pollutants and a preparation method thereof. Background Art

[0002] It is crucial to find effective means to reduce environmental pollution. Semiconductor multiphase photocatalytic technology has the advantages of no secondary pollution, relatively mild reaction conditions, and strong degradation ability. It achieves the purpose of environmental governance by utilizing solar energy conversion, especially for the rapid degradation of organic pollutants in water bodies, which can solve environmental pollution problems more efficiently and environmentally friendly. However, today's more mature semiconductor pollutant degradation catalysts generally have a large bandgap width, mainly using the higher energy ultraviolet band, and are less used in the blue-green band that accounts for a large proportion of sunlight, and the overall catalytic efficiency is low.

[0003] The research on photocatalytic technology began in 1972, when it was first discovered that TiO2 electrodes could decompose water to produce oxygen and hydrogen under sunlight. After more than 40 years of research, researchers in the field of photocatalytic technology for different processes have developed a large number of photocatalysts with excellent performance, such as TiO2, ZnO, SnO2, etc. Semiconductor materials usually dominate the field of photocatalysts because of their own structural discontinuity and excellent photoelectric properties, which makes semiconductor photocatalysts have excellent photocatalytic performance. Photocatalysts absorb light energy to cause valence band electron transitions and increase the concentration of photogenerated carriers. The process of the photocatalytic reaction is as follows: When the energy of light radiation (hv) exceeds the bandgap width (Eg) of the photocatalyst itself, the valence band electrons (e - ) are excited to transition to the conduction band, forming photogenerated electrons with reductive properties; at the same time, photogenerated holes with oxidative properties are generated in the valence band (h + ), and finally form photogenerated electron-hole pairs to participate in the catalytic reaction. The surface of the semiconductor material will have photogenerated electrons and holes that migrate to participate in the corresponding catalytic reaction. The electrons will interact with the O2 adsorbed on the surface of the material, and the holes will interact with the H2O molecules on the surface of the material to generate hydroxyl radicals (OH - ) and superoxide radicals (O2 - ).OH - Both O2 and O2 show strong oxidizing properties, which can quickly oxidize and decompose organic pollutants adsorbed on the surface of the photocatalyst, and finally mineralize the pollutants into non-toxic and harmless CO2 and H2O through a series of chemical reactions. The photocatalytic process based on semiconductor light excitation is similar to the photosynthesis of plants. Under the action of light, plants will absorb carbon dioxide and water in the air to synthesize oxygen and carbohydrates.

[0004] ZnO is a new type of multifunctional semiconductor material. It has attracted widespread attention due to its advantages of high electron mobility, low cost, simple process, high crystallinity, non-toxicity and excellent photocatalytic activity. ZnO has high plasticity, but its inherent physical properties still make it face the disadvantages of narrow spectral response range, low carrier separation rate and low visible light response in terms of light energy utilization. In recent years, research has emerged on the doping of metals and non-metallic ions to change its band structure, and metal doping to change its absorption range of the spectrum. However, the above methods require complex process levels, and the use of high-level experimental instruments and precious metal raw materials also greatly increases the cost. Therefore, it is now necessary to simplify the process and reduce the cost so that it has the prospect of industrial application.

[0005] The shortcomings of ZnO are also obvious. Its absorption spectrum is mainly in the ultraviolet band, its photon utilization rate is low, which leads to low utilization rate of visible light, and its electron relaxation time is short. These shortcomings limit the application of ZnO materials in photocatalysis. In order to improve the electron relaxation time, broadening the absorption spectrum range of ZnO is the key to its industrial application, and ultimately to better apply it to real life. Summary of the invention

[0006] The purpose of the present invention is to provide a composite material for improving the utilization rate of solar blue-green light catalytic degradation of water pollutants and a preparation method thereof. The composite material improves the utilization rate of blue-green light in sunlight by semiconductor catalysts by means of doping and composite materials.

[0007] To achieve the above object, the present invention adopts the following technical solution:

[0008] A method for preparing a composite material for improving the utilization rate of solar blue-green light catalytic degradation of water pollutants comprises: using an alkaline sodium sulfate method to decolorize wood, removing lignin inside the wood to leave cavities; and growing a ZnO nanocomposite material inside and on the surface of the treated wood by a hydrothermal method to form a ZnO composite material.

[0009] The wood is decolorized using an alkaline sodium sulfate method to remove the lignin inside the wood, leaving a cavity. The ZnO nanocomposite material is grown inside and on the surface of the treated wood using a hydrothermal method to form a composite material in which the catalyst grows inside a similar resonant cavity to improve the semiconductor catalyst's utilization of blue-green light.

[0010] Furthermore, copper ions are doped into the ZnO nanocomposite material to prepare a Cu-ZnO nanocomposite material, and the Cu-ZnO nanocomposite material is grown inside and on the surface of the treated wood to form a Cu-ZnO composite material.

[0011] By doping zinc oxide with copper ions, a Cu-ZnO nanocomposite was prepared to reduce the bandgap, allowing it to utilize longer wavelength sunlight and causing its absorption peak to red-shift.

[0012] Doping is a technique that changes the electronic structure of semiconductor materials by introducing impurity atoms, thereby reducing their band gap. The band gap of a semiconductor is the energy difference between the top of the valence band and the bottom of the conduction band, which determines the range of the material's response to light. Doping is mainly divided into n-type doping and p-type doping; n-type doping introduces elements with excess electrons (such as phosphorus and arsenic), which enter the conduction band; p-type doping introduces elements with defective electrons (holes) (such as boron and aluminum), which form positive charge carriers and increase conductivity. When impurity atoms are introduced into the semiconductor lattice, they introduce new electronic energy levels in the band structure, which are usually located in the middle of the band gap, close to the valence band or the conduction band. For n-type doping, the shallow energy levels introduced by impurity atoms are close to the conduction band, and these energy levels are called donor energy levels; for p-type doping, the shallow energy levels introduced by impurity atoms are close to the valence band, and these energy levels are called acceptor energy levels. These defect energy levels allow electrons to pass through smaller energy transitions (from the valence band to the defect energy level, or from the defect energy level to the conduction band), effectively reducing the band gap energy that the electron needs to cross. At high doping concentrations, the defect energy levels of impurity atoms may overlap with each other to form a continuous impurity energy band. This impurity energy band can significantly narrow the effective band gap, allowing the material to absorb more visible light with longer wavelengths (i.e., lower energy), thereby expanding its light absorption range. For example, in titanium dioxide (TiO2), new intermediate energy levels can be introduced into its band gap by doping non-metallic elements (such as nitrogen, carbon, sulfur) or metal elements (such as iron, cobalt, nickel). These energy levels are close to the valence band or conduction band, which effectively reduces the energy required for electron transitions, allowing the modified TiO2 to absorb part of the visible light and enhance its photocatalytic activity.

[0013] Compared with traditional semiconductor catalysts, the present invention provides a completely new direction of thinking. The band gap width is reduced to a certain extent through traditional semiconductor doping. At the same time, a new structural material is obtained through a special treatment method of wood. The Cu-ZnO nanomaterial is compounded into wood with a cavity structure to obtain a completely new composite material, which significantly improves the utilization rate of blue-green light in the visible band of sunlight, and provides a completely new idea for the future development and design of catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is an electron microscope image of the ZnO composite material provided in Example 1 of the present invention.

[0015] Figure 2 This is an electron microscope image of the Cu-ZnO composite material provided in Example 2 of the present invention.

[0016] Figure 3 The fluorescence intensity of pollutant degradation catalyzed by different composite materials.

[0017] Figure 4 is the fluorescence spectrum intensity of the catalytic degradation of pollutants under different light intensities. DETAILED DESCRIPTION

[0018] Example 1

[0019] The present embodiment provides a method for preparing a composite material for improving the utilization rate of solar blue-green light catalytic degradation of water pollutants, comprising: using an alkaline sodium sulfate method to decolorize wood, removing lignin inside the wood to leave a cavity, and growing a ZnO nanocomposite material inside and on the surface of the treated wood by a hydrothermal method to form a ZnO composite material in which the catalyst grows inside a similar resonant cavity, as shown in the electron microscope image. Figure 1 As shown, zinc oxide is grown on the treated wood by a hydrothermal method. Zinc oxide has a good and stable crystal structure and grows evenly and densely on the internal cavity surface of the wood, which allows for a larger contact surface and more reaction sites during the photocatalytic reaction.

[0020] Example 2

[0021] This embodiment provides a method for preparing a composite material for improving the utilization rate of solar blue-green light catalytic degradation of water pollutants, comprising:

[0022] First, by doping zinc oxide with copper ions to prepare a Cu-ZnO nanocomposite, the bandgap is reduced so that it can utilize longer wavelength sunlight, causing its absorption peak to red-shift;

[0023] Secondly, the wood is decolorized by alkaline sodium sulfate method, the lignin inside the wood is removed to leave a cavity, and the Cu-ZnO nanocomposite material is grown inside and on the surface of the treated wood by hydrothermal method to form a composite material in which the catalyst grows inside a similar resonant cavity, such as Figure 1 As shown, the utilization rate of blue-green light by semiconductor catalysts is improved. The cavity structure formed by the treated wood can have a certain local effect on long-wavelength light, so as to achieve the purpose of fully utilizing long-wavelength sunlight multiple times and improve the blue-green photocatalytic efficiency.

[0024] The electron microscope image of Cu-ZnO composite material is shown in Figure 2 As shown, copper / zinc oxide composite nanomaterials are grown on treated wood by a hydrothermal method. Copper zinc oxide has a flaky crystal structure and grows evenly and densely on the internal cavity surface of the wood. There are many pores inside it, which can provide a larger contact surface and more reaction sites during the photocatalytic reaction.

[0025] The following are the pollutant concentration fluorescence spectrum results of the photocatalytic experiment of Rhodamine B using 365nm, 455nm, and 530nm monochromatic LEDs as light sources. Figure 3 As shown, Figure 3 (a)(b) The fluorescence intensity of the homemade powder sample catalytically degrading pollutants, (c)(d) The fluorescence intensity of the composite material catalytically degrading pollutants under strong light. The excitation wavelength of zinc oxide powder is around 380nm. Figure 3 As shown in (a), zinc oxide powder cannot be excited under light with a wavelength of 530nm and no catalytic reaction occurs. It is weakly excited under a wavelength of 455nm and can be excited to undergo normal photocatalytic reaction under a wavelength of 365nm. Figure 3 (b) Cu-ZnO nanocomposite powder still cannot be excited at a wavelength of 530 nm, but catalytic reaction can occur at a wavelength of 455 nm, and pollutants are rapidly degraded at a wavelength of 365 nm. Figure 3 As shown in (c), after zinc oxide is compounded in wood, it can be excited at wavelengths of 365nm and 455nm and can undergo normal photocatalytic reactions, such as Figure 3 As shown in (d), after the Cu-ZnO nanocomposite powder is compounded in the wood, we can clearly observe that the pollutants are degraded at a wavelength of 530nm. This means that by doping copper and compounding wood, we can broaden the excitation wavelength spectrum of the zinc oxide-based catalyst and make it red-shifted, so that we can utilize the blue-green light that is most present in natural light.

[0026] Figure 4 The fluorescence spectrum intensity of the catalytically degraded pollutants under different light intensities, (a) (b) the fluorescence spectrum intensity of the catalytically degraded pollutants under medium light intensity, (c) (d) the fluorescence spectrum intensity of the catalytically degraded pollutants under weak light intensity; Figure 4 As shown, the fluorescence spectrum intensity results of zinc oxide composite wood and copper zinc oxide composite wood materials for catalytic degradation of pollutants under medium light intensity and weak light intensity. It can be clearly seen that the method of compounding the catalyst into wood is not affected by light intensity, and can also exert a good catalytic effect in medium and weak light environments.

[0027] The above description is only a preferred implementation manner of the present invention, but the protection scope of the present invention is not limited thereto, and any modification and replacement based on the technical solution and inventive concept provided by the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite material for improving the utilization rate of solar blue-green light catalytic degradation of water pollutants, characterized in that: include: The wood is bleached using an alkaline sodium sulfate method to remove the lignin inside the wood and leave a cavity; ZnO nanomaterials were grown inside and on the surface of the treated wood by a hydrothermal method to form ZnO nanocomposites.

2. The method for preparing a composite material for improving the utilization rate of solar blue-green light catalytic degradation of water pollutants according to claim 1, characterized in that: The ZnO nanomaterial is doped with copper ions to prepare a Cu-ZnO nanocomposite material, and then the Cu-ZnO nanocomposite material is grown inside and on the surface of the treated wood to form a Cu-ZnO nanocomposite material.

3. A composite material for improving the utilization rate of solar blue-green light catalytic degradation of water pollutants prepared by the preparation method according to claim 1 or 2.

Citation Information

Patent Citations

  • Novel ZnO / Cu2O heterojunction photocatalytic material and preparation method thereof

    CN106732617A

  • Preparation method of copper nanosheet / zinc oxide nanosheet composite material and application

    CN107159218A

  • Process for preparing copper-nickel doped nanometer zinc oxide photocatalytic material through hydrothermal method

    CN107159220A

  • Wood fiber-based composite sponge and preparation method thereof

    CN112642406A

  • Copper-doped zinc oxide nanorod, preparation method and application of copper-doped zinc oxide nanorod in piezoelectric-photocatalytic removal of organic pollutants

    CN115121257A

Cited By

  • Sulfur-doped zinc oxide nano material with broad-spectrum piezoelectric photocatalytic degradation characteristic as well as preparation method and application of sulfur-doped zinc oxide nano material

    CN121775869A

  • Preparation of SnS2-based piezoelectric catalytic material and method for degrading organic pollutants in high-salinity wastewater by using SnS2-based piezoelectric catalytic material

    CN121819872A